2019
DOI: 10.1101/652065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerated diversification correlated with functional traits shapes extant diversity of the early divergent angiosperm family Annonaceae

Abstract: Background A major goal of phylogenetic systematics is to understand both the patterns of diversification and the processes by which these patterns are formed. Few studies have focused on the ancient, species-rich Magnoliales clade and its diversification pattern. Within Magnoliales, the pantropically distributed Annonaceae are by far the most genus-rich and species-rich family-level clade, with c. 110 genera and c. 2,400 species. We investigated the diversification patterns across Annonaceae and identified tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 118 publications
(185 reference statements)
2
9
1
Order By: Relevance
“…Unlike the massive expansion of IR regions, IR regions are sometimes lost ( Ruhlman et al., 2017 ; Cauz-Santos et al., 2020 ) or contracted ( He et al., 2020 ) in the plastomes of some plant lineages and algae. Previous studies have shown that many characteristics in Annonaceae are closely associated with its high diversification rate, such as climbing habits, day-night rhythm of pollen adhesion, monoecy, and seed dispersal with seeds enclosed in single-seeded fruits ( Xue et al., 2019 ). We observed three different arrangement patterns in the plastomes of seven species within the Annona , demonstrating the diversity of plastome structures within this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the massive expansion of IR regions, IR regions are sometimes lost ( Ruhlman et al., 2017 ; Cauz-Santos et al., 2020 ) or contracted ( He et al., 2020 ) in the plastomes of some plant lineages and algae. Previous studies have shown that many characteristics in Annonaceae are closely associated with its high diversification rate, such as climbing habits, day-night rhythm of pollen adhesion, monoecy, and seed dispersal with seeds enclosed in single-seeded fruits ( Xue et al., 2019 ). We observed three different arrangement patterns in the plastomes of seven species within the Annona , demonstrating the diversity of plastome structures within this genus.…”
Section: Discussionmentioning
confidence: 99%
“…The family Annonaceae (Magnoliales) represents a study model for understanding the macroevolution of tropical forests. The family originated in the early Cretaceous (112.6-89 Ma;Xue et al, 2020). It is a large and highly diverse pantropical lineage, comprising approximately 2440 species, widely distributed in tropical lowland forests (Couvreur et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study (Couvreur et al, 2011) has suggested that lineages within Annonaceae accumulated through stable diversification rates over time, although the limited taxon sampling (4.8% of species) is likely to have resulted in an underestimation of diversification rate. More recent research (Xue et al, 2020) with improved sampling (34.2% of species) proposes an accelerated diversification in Annonaceae around 25 Ma. Certain biotic factors in Annonaceae, such as pollinator trapping, androdioecy, and single-seeded monocarp fragments, are possibly correlated with high diversification rates (Xue et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations